2020
DOI: 10.1093/cid/ciaa1420
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sociodemographic Factors, Comorbidities, and Physiologic Responses on 30-Day Mortality in Coronavirus Disease 2019 (COVID-19) Patients in Metropolitan Detroit

Abstract: Background The relationship of health disparities and comorbidities in coronavirus disease 2019 (COVID-19) related outcomes are an ongoing area of interest. This report assesses risk factors associated with mortality in patients presenting with Covid-19 infection and healthcare disparities. Methods A retrospective cohort study of consecutive patients presenting to emergency departments within an integrated health system who t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 11 publications
4
22
0
Order By: Relevance
“…The etiology of an age-related effect on poor outcomes in patients with COVID-19 has been described to be related to increasing baseline inflammation, possibly resulting from increasing levels of senescent cells with age. Senescent cells can activate endothelial cells lining capillaries in the lungs and increase expression of natural killer cell receptor ligands that recruit natural killer- (56-72% Black patients in the Detroit metropolitan area) (15,17,37). In fact, our data suggested that Black patients had significantly lower odds of death than White patients, similar to results of a smaller study conducted at HFHS by Miller et al (37).…”
Section: Age and Outcomes From Covid-19supporting
confidence: 87%
See 1 more Smart Citation
“…The etiology of an age-related effect on poor outcomes in patients with COVID-19 has been described to be related to increasing baseline inflammation, possibly resulting from increasing levels of senescent cells with age. Senescent cells can activate endothelial cells lining capillaries in the lungs and increase expression of natural killer cell receptor ligands that recruit natural killer- (56-72% Black patients in the Detroit metropolitan area) (15,17,37). In fact, our data suggested that Black patients had significantly lower odds of death than White patients, similar to results of a smaller study conducted at HFHS by Miller et al (37).…”
Section: Age and Outcomes From Covid-19supporting
confidence: 87%
“…Senescent cells can activate endothelial cells lining capillaries in the lungs and increase expression of natural killer cell receptor ligands that recruit natural killer- (56-72% Black patients in the Detroit metropolitan area) (15,17,37). In fact, our data suggested that Black patients had significantly lower odds of death than White patients, similar to results of a smaller study conducted at HFHS by Miller et al (37).…”
Section: Age and Outcomes From Covid-19supporting
confidence: 87%
“…Acute kidney injury (AKI) continues to affect between 10 and 40% of in-hospital coronavirus disease 2019 (COVID- 19) patients (1)(2)(3)(4). Since the beginning of the COVID-19 pandemic, mostly elderly individuals with many comorbidities have developed AKI and died (5,6). The adaptation of mechanisms to the kidneys that respond to hemodynamic changes, inflammation, and other stress-inducing situations, perform worse in cases of previous kidney affectation, diabetes, heart failure, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This trend supports previous studies in China, Italy, and the United States which reported that men and old age are two important risk factors. [12][13][14] In our paper, the proportion of underlying diseases is higher in men than in women, and the proportion of underlying diseases is particularly high in the elderly, which is the main reason for the severity and mortality of COVID-19. In our study, patients living in metropolitan areas did not have significantly increased severity of COVID-19 compared to other patients, and there were significantly lower mortality rates in metropolitan areas.…”
Section: Discussionmentioning
confidence: 58%